Potato and sweetpotato in Africa: transforming the value chains for food and nutrition security - Low, Jan W.; Nyongesa, M.; Quinn, S.; Parker, M. (CAB International, 2015)
This book is based on papers presented at the Ninth Triennial African Potato Association Conference, Naivasha, Kenya, 30 June-4 July 2013.The book focuses on the policies for germplasm exchange, food security and trade in Africa, seed systems, breeding and disease management and postharvest management, processing technologies and marketing systems of potato and sweet potato. The nutritional value and changing behaviors of potato and sweet potato crops are also discussed.